Differential viral loads of human papillomavirus 16 and 58 infections in the spectrum of cervical carcinogenesis. Issue 2 (1st March 2006) - Lai, H. C.; Peng, M. Y.; Nieh, S.; Yu, C. P.; Chang, C. C.; Lin, Y. W.; Sun, C. A.; Chu, T. Y.
Abstract : Human papillomavirus (HPV) load was reported to be related to the severity of cervical neoplasia but with controversy. The viral load–disease severity relationship was showed in HPV 16, but no study was made in HPV 58, the second most prevalent HPV in cervical cancer in East Asia. We studied cervical HPV loads in HPV 16– and HPV 58–infected cases of normal, low-grade squamous intraepithelial lesions (LSIL), high-grade squamous intraepithelial lesions (HSIL), and invasive cervical cancer (CC) by using quantitative polymerase chain reaction (Q-PCR) with type-specific primers in defined cell number. With the exception of HPV 16 infection in normal, viral loads varied greatly in each disease regardless of genotypes. The load of HPV 16 differed significantly among disease severities, with a dramatic increase from normal (1.14 ± 2.25 copies/cell) to LSIL, HSIL, and CC (1599 ± 2301, 7489 ± 24, 087 and 1878 ± 2979 copies/cell, respectively) ( P < 0.01). No significant difference was noted among different HPV 58 infections, with loads in normal, LSIL, HSIL, and CC of 503 ± 641, 7951 ± 27, 557, 353 ± 744, and 1139 ± 2895 copies/cell, respectively. In comparison with HPV 16, HPV 58 subclinical infection confers a significant higher load ( P < 0.01). Different HPV types behave differentially in the spectrum of cervical carcinogenesis. Unlike HPV 16, the infection load of HPV 58 does not correlate to the clinical severity. The wide variation of HPV loads among different HPV types and among squamous intraepithelial lesions and CC makes the viral load test unrealistic in differentiating different severities of cervical neoplasia.